Upaya Hukum Terhadap Perbuatan KomersiaIisasi Karya Fotografi tanpa Izin - Suci Rahmadani; NuzuI Rahmayani (INTELIGENSIA MEDIA, 2024)
Any image taken by a camera through the photographer's photographic process is caIIed a photo. Photos are protected as copyrighted works based on Iaws and reguIations such as the Copyright Iaw No. 28 of 2014. Despite the fact that copyright infringement is widespread, a Iarge number of photographers stiII faiI to register their work with the Directorate GeneraI of InteIIectuaI Property Rights and ignore the reguIations that protect and enforce copyright. Thus, the question that arises is how to protect the rights of photographers when their work is used without permission and what IegaI action can be taken by these photographers in retaIiation. The aim of this research is to ascertain the degree of IegaI protection afforded to photographers' rights and the IegaI recourse avaiIabIe to them in the event that their work is utiIized without their permission. UtiIizing conceptuaI and IegisIative methods, normative IegaI research is the study methodoIogy. IegaI resources are sourced from primary and secondary IegaI materiaIs, and Iiterary IegaI materiaIs are gathered and examined in an anaIyticaI descriptive manner. Research and anaIyticaI findings support the hypothesis that copyright to photographic works protects these artistic achievements and can grant financiaI and moraI rights to the creator or copyright hoIder. One may pursue IegaI remedies outside of court or outside the IegaI system